2020
DOI: 10.1097/md.0000000000022598
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shockwave therapy combined with multiple drilling and intramedullary drug injection for treating early-stage Femur Head Necrosis

Abstract: Background: Early diagnosis and treatment of the osteonecrosis of the femoral head (ONFH), a refractory disease, is imperative to prevent femoral head collapse; however, the existing solutions remain controversial. This study assessed the safety and efficacy of extracorporeal shock wave therapy (ESWT) combined with multiple drilling and intramedullary drug injection, a novel cocktail therapy, as a randomized controlled trial (RCT) model to postulate an alternative therapy for patients with early-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The operations adopted by our hospital for early and medium-term ONFH mainly include MSFLD and hip arthroscopy + MSFLD. MSFLD, that is, using 3.0 Kirschner wire, for the femoral head necrosis area, fan-shaped drilling decompression in different directions, different depths, and the number of porous channels [19][20][21] . In most cases, 3-5 holes were drilled, and in a few cases with small necrosis, 2 holes were drilled.…”
Section: Analysis Of Survival Years Of Femoral Headmentioning
confidence: 99%
“…The operations adopted by our hospital for early and medium-term ONFH mainly include MSFLD and hip arthroscopy + MSFLD. MSFLD, that is, using 3.0 Kirschner wire, for the femoral head necrosis area, fan-shaped drilling decompression in different directions, different depths, and the number of porous channels [19][20][21] . In most cases, 3-5 holes were drilled, and in a few cases with small necrosis, 2 holes were drilled.…”
Section: Analysis Of Survival Years Of Femoral Headmentioning
confidence: 99%
“…ESWT was suggested to promote angiogenesis, bone remodelling and regenerative effect in ONFH [ 31 , 32 ]. Clinically, studies have shown that ESWT is effective in the treatment of early stage ONFH [ 33 , 34 ]. Physical ESWT can enhance bone marrow stromal cell differentiation into osteoprogenitors by transforming growth factor-beta 1 induction [ [35] , [36] , [37] ].…”
Section: Introductionmentioning
confidence: 99%